Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Akuntansi Mengikuti Ujian Sertifikasi Chartered Accountant (CA) (Studi Kasus Pada Politeknik Negeri Manado) - Mongilala, Joshua Fanuel (Universitas Pendidikan Ganesha, 2021)
Chartered Accountant (CA) Indonesia is a professional accountant qualification according to international standard guidelines. The benefit of this research is as input for: accounting students who are interested in taking the CA certification exam, in developing the implementation of the CA certification exam, State Polytechnic Accounting Department. The approach used is an inductive qualitative approach, in order to describe the factors that influence the interest of accounting students who are interested in taking the CA certification exam. Data collection techniques are carried out through passive participation observation, unstructured interviewswith 5 (five) key informants, and documentation. Data analysis was performed using qualitative analysis techniques through data reduction activities, data presentation, and conclusion / verification. The results showed that the interest is influenced by subjective norm factors which include an encouragement and a will from oneself; attitudes towards behavior factors, which include open opportunities in entry competitions and careers in local and foreign companies, being able to develop themselves as professional accountants in accordance with international standards; Perceived behavioral control factors include the belief in taking a certification exam even though it requires a fairly large allocation of time and costs, with the consideration that working time while studying can be done together or choosing to postpone work because they want to prepare themselves for the CA certification exam, while the amount of the cost is considered to be reasonable.Â